Targeted and untargeted metabolomics reveals deep analysis of drought stress responses in needles and roots of Pinus taeda seedlings - Wu, Chu; Wang, Yun; Sun, Honggang (Frontiers in Plant Science, 2023)
Drought stress is one of major environmental stresses affecting plant growth and yield. Although Pinus taeda trees are planted in rainy southern China, local drought sometime occurs and can last several months, further affecting their growth and resin production. In this study, P. taeda seedlings were treated with long-term drought (42 d), and then targeted and untargeted metabolomics analysis were carried out to evaluate drought tolerance of P. taeda. Targeted metabolomics analysis showed that levels of some sugars, phytohormones, and amino acids significantly increased in the roots and needles of water-stressed (WS) P. taeda seedlings, compared with well-watered (WW) pine seedlings. These metabolites included sucrose in pine roots, the phytohormones abscisic acid and sacylic acid in pine needles, the phytohormone gibberellin (GA4) and the two amino acids, glycine and asparagine, in WS pine roots. Compared with WW pine seedlings, the neurotransmitter acetylcholine significantly increased in needles of WS pine seedlings, but significantly reduced in their roots. The neurotransmitters L-glutamine and hydroxytyramine significantly increased in roots and needles of WS pine seedlings, respectively, compared with WW pine seedlings, but the neurotransmitter noradrenaline significantly reduced in needles of WS pine seedlings. Levels of some unsaturated fatty acids significantly reduced in roots or needles of WS pine seedlings, compared with WW pine seedlings, such as linoleic acid, oleic acid, myristelaidic acid, myristoleic acid in WS pine roots, and palmitelaidic acid, erucic acid, and alpha-linolenic acid in WS pine needles. However, three saturated fatty acids significantly increased in WS pine seedlings, i.e., dodecanoic acid in WS pine needles, tricosanoic acid and heptadecanoic acid in WS pine roots. Untargeted metabolomics analysis showed that levels of some metabolites increased in WS pine seedlings, especially sugars, long-chain lipids, flavonoids, and terpenoids. A few of specific metabolites increased greatly, such as androsin, piceatanol, and panaxatriol in roots and needles of WS pine seedlings. Comparing with WW pine seedlings, it was found that the most enriched pathways in WS pine needles included flavone and flavonol biosynthesis, ABC transporters, diterpenoid biosynthesis, plant hormone signal transduction, and flavonoid biosynthesis; in WS pine roots, the most enriched pathways included tryptophan metabolism, caffeine metabolism, sesquiterpenoid and triterpenoid biosynthesis, plant hormone signal transduction, biosynthesis of phenylalanine, tyrosine, and tryptophan. Under long-term drought stress, P. taeda seedlings showed their own metabolomics characteristics, and some new metabolites and biosynthesis pathways were found, providing a guideline for breeding drought-tolerant cultivars of P. taeda.